HOW TECHNOLOGY IS EMPOWERING PRODUCTIVE ZAKAT RECIPIENT AT BAITUL MAL ACEH? - Eka Nurlina; Nurma Sari; Teuku Muhammad Syahrizal; Hendra Halim; Khairil Umuri (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
Zakat is an important instrument and plays a role in improving community welfare. The distribution of productive zakat properly and the use of technology in empowerment activities can support the improvement of the mustahiq economy. This study aims to analyze the distribution of productive zakat by Baitul Mal Aceh and the role of technology by mustahiq in improving welfare. This study uses a qualitative descriptive method by interviewing Baitul Mal Aceh, 40 productive zakat mustahiq and academics. The data obtained are explained using interactive techniques. The results of the study indicate that the business capital assistance program managed by Baitul Mal Aceh consists of 3 programs, namely mustahiq empowerment through the provision of ultra-micro capital, Zakat Family Development (ZFD) and mustahiq empowerment through partners. The three programs have not had a significant impact on improving the welfare of mustahiq. This is due to several things, namely mustahiq have not been able to develop their businesses, have not been maximized, lack of supervision and assistance to mustahiq businesses, and do not have a good mentoring concept. The use of technology that is not optimal is also an obstacle in improving the welfare of mustahiq. Therefore, comprehensive support is needed from various parties such as the government, society and other institutions that support the realization of productive zakat in improving the welfare of mustahiq.